A comparative quantitative genetic study between two populations of a fly Calliphora vicina (R-D,1830) (Diptera: Calliphoridae) in Iraq - Hussein, M. Prism; Shatha, A. Mahdi; Riyad Ali Okaily (Caspian Journal of Environmental Sciences)
The quantitative genetic relationship between two populations of the fly Calliphoravicina was studied, specimens of which were collected from some areas of waist and southern Iraq.In this study, the geometric morphometric system for wing shape and size was used to detect quantitative genetic variations in the shape, size and area of the right wing of the fly specimens.Rate central size of the right wing was 1412.4, 1423.7 microns for specimensfrom the waist and southern regions of Iraq, respectively.The results of the statistical analysis using the F and T tests showed that there were no significant differences in rate right wing central size between the specimens of the study areas, except for one significant difference found in one of the insect specimens of the southern region than it is in the specimens of the waist region.It was also noted that there were very few significant differences in the shape and size of the right wing of some insect specimens for that area due to their impact on the different environmental conditions in the areas from which the specimens were collected when using ANOVA analysis.